In the poetry of the briefing book in the news of Granada to San Aldin Ibn al-Khatib Andalusia (T 776): study in the philosophy of beauty - Ridah Karim, Nardeen; Ridha Karim, Haidar (Al-Adab Journal, 2019)
There is a real difference between a large segment of the population of recipients on the assessment of the literary text aesthetically evaluated, and this assessment stems from the intuition of the recipient and his sense of the aesthetic sense of the missing text, and the extent of interaction with the sense and the pulse and emotion, as well as the questioning of its devices and disassociated to identify the aesthetic touch in the text sought by The writer behind his totalitarianism, the dualism between the moral game of the Tory and its vocabulary stored in the subconscious area of ​​the innovative art of organization and consistency.